Soluble Molecularly Imprinted Nanorods for Homogeneous Molecular Recognition - Liang, Rongning; Wang, Tiantian; Zhang, Huan; Yao, Ruiqing; Qin, Wei (Frontiers in Chemistry, 2018)
Nowadays, it is still difficult for molecularly imprinted polymer (MIPs) to achieve homogeneous recognition since they cannot be easily dissolved in organic or aqueous phase. To address this issue, soluble molecularly imprinted nanorods have been synthesized by using soluble polyaniline doped with a functionalized organic protonic acid as the polymer matrix. By employing 1-naphthoic acid as a model, the proposed imprinted nanorods exhibit an excellent solubility and good homogeneous recognition ability. The imprinting factor for the soluble imprinted nanoroads is 6.8. The equilibrium dissociation constant and the apparent maximum number of the proposed imprinted nanorods are 248.5 μM and 22.1 μmol/g, respectively. We believe that such imprinted nanorods may provide an appealing substitute for natural receptors in homogeneous recognition related fields.